SOSIALISASI DAN PENANAMAN DALAM RANGKA REHABILITASI HUTAN PANTAI BERSAMA MASYARAKAT DI DESA HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Andjela Sahupala; Yulianus D. Komul; Irwanto Irwanto; Fanny Soselisa; Lesly Latupapua; Fredy Hendry Louhenapessy (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The aim of planting coastal vegetation in Hatusua Village is to rehabilitate damaged environmental conditions and support the recovery of coastal ecosystems. Beach forest rehabilitation activities are carried out in 2 stages, namely: First Stage; Socialization, training and assistance for farmer groups and the second stage is planting in the designated rehabilitation area. The species used in coastal forest rehabilitation are: Ketapang (Terminalia catappa), Hutung (Barringtonia asiatica) and Bintangur Pantai (Calophyllum inophyllum). Socialization, Training and Assistance of Farmers and Community Groups is carried out by the lecturer staff of the Department of Forestry, University of Pattimura to increase the knowledge and skills of coastal communities in carrying out beach forest rehabilitation. Planting activities are carried out jointly by academics, village government and the community. The participation of all parties needs to be increased in maintenance of tree species planted so that the plants can grow well in the field. In addition, cooperation is needed in monitoring various destructive community practices, which have a negative impact on the preservation of the beach forest of Hatusua Village.